PENINGKATAN PROFESIONALISME GURU KELOMPOK BERMAIN SRIKANDI ROWODADI - Retno Wulandari; Mayang Belia Sameto; Sumantri (Yayasan Wayan Marwan Pulungan, 2023)
Professional teachers can produce students who are competent and compete in this era of globalization. In line with the motto of KB Sebiduk Sehaluan Srikandi,